Women Entrepreneurs in Kathmandu Valley - Sidgel, Minu (PYC Nepal Journal of Management, 2017)
Women entrepreneurship entails business ownership and business creation that empowers women economically. It increases their economic strength as well as position in the society. Women entrepreneurs face number of problems to start and sustain business enterprises. They lack access to capital, training, technical and financial knowledge. This research looks at the personnel characteristics of women entrepreneur in Kathmandu valley and their motivational factor to start a business. It also looks at some of the problems faced by women entrepreneur in relation to capital formation and technical knowhow. This study used primary data and it was collected through a set of questionnaire and interviews of women entrepreneurs registered with the DSCI, FNCCI, FWEAN and Nepal Chamber of Commerce within Kathmandu valley.